2004
DOI: 10.1007/s00427-004-0403-7
|View full text |Cite
|
Sign up to set email alerts
|

Connexin43 orthologues in vertebrates: phylogeny from fish to man

Abstract: The gap junction protein connexin43 (Cx43) is widely expressed in all vertebrate species; however, in ventricular myocardium, Cx43 expression is restricted to mammalian species only, where it provides the molecular correlate for both electrical conduction and synchronization of the repolarization process. The evolutionarily "late" appearance of Cx43 in the heart suggests physiological adaptation to euthermia with its concomitant demands related to increased cardiovascular output. We tested to what extent mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…We think this citation describes the puzzlement that many researchers (for ourselves, we could even say confusion) have felt when looking at the different and ever-increasing number of sequences from an increasing number of species, now also including the nonvertebrate group of tunicates [70,73]. A potential reason for the puzzlement could come from the fact that some of the connexins, like orthologs of Cx36 and 43, also have a high degree of conservation in the variable domains, and can therefore easily be recognized across the vertebrates [66,67,74,75]. From this observation, one might assume that this should also be valid for other connexins.…”
Section: Differences In Sequences and The Puzzlementmentioning
confidence: 94%
“…We think this citation describes the puzzlement that many researchers (for ourselves, we could even say confusion) have felt when looking at the different and ever-increasing number of sequences from an increasing number of species, now also including the nonvertebrate group of tunicates [70,73]. A potential reason for the puzzlement could come from the fact that some of the connexins, like orthologs of Cx36 and 43, also have a high degree of conservation in the variable domains, and can therefore easily be recognized across the vertebrates [66,67,74,75]. From this observation, one might assume that this should also be valid for other connexins.…”
Section: Differences In Sequences and The Puzzlementmentioning
confidence: 94%
“…Measurements of electrical conductance between the heterologous cell-pairs revealed that the level of coupling was rather poor. Because of a very high amino acid homology of Cx43 proteins in general [25], this low conductance is unlikely to result from species differences. In our model no docking problems have to be expected since rat Cx43 and canine Cx43 showed an overall identity of 97.1%, with only one residue differing in the extracellular domain (data not shown).…”
Section: Role Of Cell-to-cell Couplingmentioning
confidence: 94%
“…Beyer et al [1987] published hydropathicity plots of Cx43, delineating the hydrophobic membrane spanning domains in their model of connexin topology. Since then, various Cx43 topology predictions have been published [Yancey et al, 1989;Laird and Revel, 1990;Yeager and Gilula, 1992;Yeager, 1998;van der Heyden et al, 2004]. Web transmembrane prediction tools HMMTOP, TMHMM, SOSUI, Tmpred, and TopPred (ExPASy Proteomics tools: http://www.…”
Section: Gja1 Mutations and Their Relevance To The Connexin 43 Proteinmentioning
confidence: 99%